High frequency words in English textbooks for Indonesian senior high schools - Rizki Meliani Rustan; Erna Andriyanti (Studies in English Language and Education, 2021)
This content analysis study focused on three main purposes, including to analyse the High Frequency Words (HFWs) of Dolch’s list in reading texts from three English textbooks of Indonesian senior high schools, to analyse the language features of HFWs in reading texts of the English textbooks, and to propose strategies that can be used in teaching HFWs. The reading texts were grouped into three types including recount text, narrative text, and descriptive text. The reading texts were further analysed using an online word-counter to find out the HFWs of Dolch’s list in the texts. The findings show that there were 124 words found as the HFWs. The HFWs found were mostly articles, prepositions, pronouns, nouns, verbs, adverbs, adjectives, and conjunctions. Those were the most frequent words that should be known by students. Moreover, the language features of HFWs in each text were varied according to its context and the types of the texts. Hence, some strategies could be applied to facilitate English teachers in teaching HFWs, such as the word card strategy and direct teaching strategy, so that their students master the HFWs. The implication of this study also suggested textbook writers to provide additional content in textbooks such as the word list of HFWs.